Effective Bookkeeping Using Online-Based Application to Leverage the Competitive Advantage of MSMEs in Ciledug District - Riyani, Etik Ipda; Tantri, Sakina Nusarifa; Hardiana, Nadhira; Widiastuti, Yeni; Muktiyanto, Ali (Journal of The Community Development in Asia, 2023)
The purpose of this community service is to provide assistance in improving knowledge and skills for MSME actors in Ciledug in carrying out bookkeeping using online-based application. This assistance activity is carried out in four stages, the first stage is assistance in general bookkeeping for manufacture and production businesses. The second stage is assistance for manufacture businesses. The third stage is assistance for retail businesses, while the fourth stage is consultation session. The assistance program included monitoring and evaluation to see the effectiveness of this program in helping MSME productivity and improving competitive advantages. The results of this assistance program indicated that MSME actors are being capable to record the financial transaction using online-based bookkeeping and produce financial reports using online-based application. The monitoring and evaluation stage resulted that MSMEs can improve their efficiency, effectiveness, and productivity by using financial information produced by online-based application. Therefore, MSMEs can achieve their own competitive advantages.